2003
DOI: 10.1590/s0036-46652003000400004
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary study of the prevalence of intestinal parasites in immunocompromised patients with and without gastrointestinal manifestations

Abstract: SUMMARYThe objective of the present study was to determine the prevalence of the intestinal parasites most commonly found in immunocompromised patients. A group of 111 individuals with acute lymphoid leukaemia (ALL), chronic myeloid leukaemia (CML), human immunodeficiency virus (HIV) and other immunocompromised conditions (principally haematological disorders) was selected. A battery of tests was performed on each individual to identify the presence of parasites (three stool specimens with saline solution and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
61
5
7

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(78 citation statements)
references
References 16 publications
1
61
5
7
Order By: Relevance
“…In these patients, parasites such as Cryptosporidium parvum, Enterocytozoon bieneusi, Encephalytozoon intestinalis and Strongyloides stercoralis may disseminate to other organs such as bile and liver ducts, producing symptomatology specific to the organ affected (Botero et al 2003). In this study, intestinal parasitosis was diagnosed by examination of stool samples, using very simple methods in which the forms of the parasites were observed.…”
Section: Discussionmentioning
confidence: 99%
“…In these patients, parasites such as Cryptosporidium parvum, Enterocytozoon bieneusi, Encephalytozoon intestinalis and Strongyloides stercoralis may disseminate to other organs such as bile and liver ducts, producing symptomatology specific to the organ affected (Botero et al 2003). In this study, intestinal parasitosis was diagnosed by examination of stool samples, using very simple methods in which the forms of the parasites were observed.…”
Section: Discussionmentioning
confidence: 99%
“…Botero et al (32) found a 32% frequency of parasites in a population with some type of immunological deficiency, including HIV infection. Reduced intestinal parasite prevalence has been observed in Brazil and worldwide since the early HAART years even when specific methods are included (51,52).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have connected serious or disseminated intestinal parasitic infections to immunosuppression, including AIDS, although several aspects remain obscure (12,26,(32)(33)(34)(35)(36)(37). This study aimed to better clarify the participation of intestinal parasites and their correlation with Various studies have associated intestinal parasites with education levels.…”
Section: Discussionmentioning
confidence: 99%
“…Microsporidia may present urinary, pulmonary or disseminate infections includingsinusitis, encephalitis, tracheobronchitis, nephritis, hepatitis, myositis, ocular and stromal keratitis, increasingly are identified by E. intestinalis spp Human microsporidiosis occurs worldwide, but data on the prevalence and geographic distribution of microsporidial infections are still incomplete and very diverse due to the use of different diagnostic methods, no specialized personal and the focus of parasitic studies on common parasites 12 . Microsporidia have been less reported among cancer patients worldwide 13 ; moreover, no studies have been conducted on the prevalence of Microsporidia in cancer patients in Iran despite its occurrence in HIV + population. It has been reported that immunosuppressive therapy may be associated with higher risk of severe parasitic infections 13,14 .…”
Section: Frequency Of Microsporidial Infection In Immunocompromised Pmentioning
confidence: 99%
“…Microsporidia have been less reported among cancer patients worldwide 13 ; moreover, no studies have been conducted on the prevalence of Microsporidia in cancer patients in Iran despite its occurrence in HIV + population. It has been reported that immunosuppressive therapy may be associated with higher risk of severe parasitic infections 13,14 . To date, many papers reported microsporidial infection in HIV + patients 9 , but we did not have any precise information of intestinal microsporidiosis infection in this patient in Iran except rare studies that were carried out by Agholiet al, Mirjalali and Ghorbanzadeh [15][16][17][18] .…”
Section: Frequency Of Microsporidial Infection In Immunocompromised Pmentioning
confidence: 99%